Electrochemical fabrication of carbon nanotube/polyaniline hydrogel film for all-solid-state flexible supercapacitor with high areal capacitance. Issue 47 (3rd November 2015) - Zeng, Sha; Chen, Hongyuan; Cai, Feng; Kang, Yirang; Chen, Minghai; Li, Qingwen
Abstract : CNT film prepared via a floating catalyst CVD method was activated by an electrochemical strategy for better PANI growth. Both this CNT/PANI hydrogel film electrode and a flexible symmetric supercapacitor based on this electrode material exhibited high areal capacitance. Abstract : Carbon nanotube (CNT) film is a favorable kind of substrate in flexible electric devices because of its superior flexibility, favorable mechanical strength and excellent electrical conductivity. Moreover, since the conductive polymer polyaniline (PANI) possesses a high capacitance and is easy to manufacture, it is always a favored material in the field of supercapacitors. In this research, CNT film synthesized via a floating catalyst chemical vapor deposition method could be further activated by its electrochemical re-expansion to achieve better porosity and higher specific area, in order to obtain an all-solid-state flexible supercapacitor with a higher area capacitance. In comparison with the pristine CNT film decorated with PANI, electrochemically fabricated CNT hydrogel film with PANI deposition had a higher specific area capacitance of 680 mF cm −2 at 1 mA cm −2 . The all-solid-state supercapacitor that was synthesized from this composite film exhibited a high specific area capacitance of 184.6 mF cm −2 at 1 mA cm −2, which was higher than many similar supercapacitors. The rolling test showed that this supercapacitor maintained its high capacitance even under conditions of rolling. After 500 charge–discharge cycles, it also retained its high coulombic efficiency and specific area capacitance. This all-solid-state supercapacitor shows great potential in the field of energy storage devices.